2019
DOI: 10.1101/642959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Redundant and specific roles of cohesin STAG subunits in chromatin looping and transcription control

Abstract: Cohesin is a ring-shaped multiprotein complex that is crucial for 3D genome organization and transcriptional regulation during differentiation and development. It also confers sister chromatid cohesion and facilitates DNA damage repair. Besides its core subunits SMC3, SMC1A and RAD21, cohesin contains in somatic cells one of two orthologous STAG subunits, SA1 or SA2. How these variable subunits affect the function of the cohesin complex is still unclear. SA1-and SA2-cohesin were initially proposed to organize … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
(111 reference statements)
1
1
0
Order By: Relevance
“…Consistent with our findings, it has recently been reported that cohesin STAG1 and cohesin STAG2 contribute to chromatin differently (Casa et al, 2019;Viny et al, 2019;Cuadrado et al, 2019;Kojic et al, 2018), with cohesin STAG1 contributing more to TAD organisation than cohesin STAG2 . Cohesin STAG1 has also been shown to be more resistant to biochemical salt extraction from chromatin than cohesin STAG2 (Kojic et al, 2018), but whether this property is related to the long chromatin residence time of acetylated cohesin STAG1 reported here is unknown.…”
Section: Acetylated Cohesin Stag1 Complexes Are Protected From Wapl Bsupporting
confidence: 93%
“…Consistent with our findings, it has recently been reported that cohesin STAG1 and cohesin STAG2 contribute to chromatin differently (Casa et al, 2019;Viny et al, 2019;Cuadrado et al, 2019;Kojic et al, 2018), with cohesin STAG1 contributing more to TAD organisation than cohesin STAG2 . Cohesin STAG1 has also been shown to be more resistant to biochemical salt extraction from chromatin than cohesin STAG2 (Kojic et al, 2018), but whether this property is related to the long chromatin residence time of acetylated cohesin STAG1 reported here is unknown.…”
Section: Acetylated Cohesin Stag1 Complexes Are Protected From Wapl Bsupporting
confidence: 93%
“…compared to the gene-body or the TTS [80], suggesting that promoters are at the core of regulatory activity. Secondly, several HiC studies reported loop formation within a distinct gene, that is chromatin contacts between the TSS of gene x to intragenic positions of gene x up to its TTS, whereas loops from the TTS to other genomic locations have not been reported [81,82].…”
Section: Discussionmentioning
confidence: 99%